The Sociology Of Islamic Education In Shaping Learners' Social Behavior: A Theoretical Perspective Of Peter L. Berger - Salsabiila Roudlotul Firdaus; Ommar Sharief; Tarjono; Benny Prasetiya (Al-Hikmah: International Journal of Islamic Studies, 2026)
The moral degradation and declining social empathy among students in the disruption era require Islamic educational institutions to move beyond their traditional role as centers of doctrinal knowledge transmission and function as effective agents of socialization. This study examines the role of the sociology of Islamic education in shaping students’ social behavior through the perspective of Peter L. Berger’s social construction of reality theory. Using a qualitative approach with a library research design, data were collected from reputable books and scholarly journals. Data validity was ensured through source and theory triangulation, while analysis was conducted using content analysis techniques involving data reduction, concept classification, interpretation, and conclusion drawing.The findings reveal that the formation of Islamic social behavior is a continuous dialectical process encompassing three stages. First, externalization occurs when educators articulate religious values through exemplary conduct (uswah hasanah). Second, objectivation involves institutionalizing these values within school culture, regulations, and the hidden curriculum. Third, internalization refers to students’ absorption of these objective realities into their subjective consciousness, resulting in moral habituation. The study concludes that students’ social behavior is shaped through institutional sociological processes that integrate these three dialectical stages.